The Replication of Academic Database System using Linux Ubuntu Server Technology - Ajulio Padly Sembiring (Universitas Muhammadiyah Sumatera Utara, Indonesia, 2020)
Replication system is a system that is currently widely used, with the advantage of data security that can be guaranteed security. The replication of the Web-Based Student Academic System Database is implemented using VMWare workstation 9.0. By using Ubuntu Server 12.04 which is a server, there are three servers that are built including the master server, slave 1 and slave 2, with the three servers synchronized and replicated automatically in the system, with a system like this it is hoped that the data inside is guaranteed the security and distribution are faster. The system is implemented using a Local Area Network (LAN) using a client, which is accessed from the browser on the client